Review of the leafhopper genus Pythamus Melichar (Hemiptera: Cicadellidae: Evacanthinae) in the Indian subcontinent - Viraktamath, C. A.; Webb, M. D. (Zootaxa, 2007)
The genus Pythamus Melichar (type species: P. dealbatus Melichar) is redefined. The genus Dussana Distant (type species: D. quaerenda Distant) is treated as a junior synonym of Pythamus. Three new species, Pythamus biramosus sp. nov. (India: Karnataka), P. bispinosus sp. nov. (India: Tamil Nadu, Kerala) and P. montanus sp. nov. (India: Tamil Nadu) in addition to P. dealbatus are described and illustrated. Dussana quaerenda is treated as a junior synonym of P. dealbatus. Dussana assamensis Ramakrishnan is transferred to the genus Onukia. A key to species of Pythamus is also provided.